(untitled) (Experimental biology, 2015)
The facts about change of hydroplasma of water properties under action of electromagnetic and electrostatic field of the TV in comparison with various kinds of biogenic water are presented. The prospect of anti-entropy space formation round vessels with biogenic water is come out.